Adult congenital heart disease: education and preparation of nurses. (2nd January 2022) - Lotto, Robyn
Abstract : In this month's BANCC feature, Robyn Lotto, senior lecturer, advanced cardiac nurse practitioner and committee member of BANCC, reflects on the educational needs of cardiac nurses caring for patients with congenital heart defects.